2020
DOI: 10.1002/qj.3827
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of tropical waves and wave forcing of the QBO in the QBOi models

Abstract: We analyze the stratospheric waves in models participating in phase 1 of the Stratosphere-troposphere Processes And their Role in Climate (SPARC) Quasi-Biennial Oscillation initiative (QBOi). All models have robust Kelvin and mixed Rossby-gravity wave modes in winds and temperatures at 50 hPa and represent them better than most of the Coupled Model Intercomparison Project Phase 5 (CMIP5) models. There is still some spread among the models, especially concerning the mixed Rossby-gravity waves. We attribute the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 76 publications
7
67
0
Order By: Relevance
“…A much better QBO was obtained in a previous version of this model, CESM1‐WACCM, when the vertical resolution was doubled in the troposphere and lower stratosphere (Garcia & Richter, ). Holt et al () has demonstrated a clear relationship between the wave forcing from resolved waves in the lower stratosphere and vertical resolution in QBOi models. Similar dependence of lower stratospheric wave forcing on horizontal resolution was not found.…”
Section: Summary and Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…A much better QBO was obtained in a previous version of this model, CESM1‐WACCM, when the vertical resolution was doubled in the troposphere and lower stratosphere (Garcia & Richter, ). Holt et al () has demonstrated a clear relationship between the wave forcing from resolved waves in the lower stratosphere and vertical resolution in QBOi models. Similar dependence of lower stratospheric wave forcing on horizontal resolution was not found.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Similar dependence of lower stratospheric wave forcing on horizontal resolution was not found. Holt et al () also showed that even models that have ample wave momentum flux entering the lower stratosphere seem to underestimate the contribution of these waves to the QBO driving in the upper stratosphere, which suggests that factors such as vertical resolution and numerical dissipation might influence the effectiveness of Kelvin and mixed Rossby GWs in driving the QBO.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weaknesses in gravity wave parameterization methods may be partly to blame. Evidence suggests that increasing model vertical resolution improves the simulation of the QBO (Giorgetta et al, 2002;Richter et al, 2014), because resolved tropical wave drag increases at higher vertical resolution (Holt et al, 2016(Holt et al, , 2020. These resolved waves may include Kelvin waves, mixed Rossby-gravity waves, and inertia-gravity waves.…”
Section: Introductionmentioning
confidence: 99%